Influence of rotator cuff integrity on loading and kinematics before and after reverse shoulder arthroplasty. (2nd December 2021) - Péan, Fabien; Favre, Philippe; Goksel, Orcun
Abstract: Reverse Shoulder Arthroplasty has become a very common procedure for shoulder joint replacement, even for scenarios where an anatomical reconstruction would traditionally be used. Our hypothesis is that implanting a reverse prosthesis with a functional rotator cuff may lead to higher joint reaction force (JRF) and have a negative impact on the prosthesis. Available motion capture data during anterior flexion was input to a finite-element musculoskeletal shoulder model, and muscle activations were computed using inverse dynamics. Simulations were carried out for the intact joint as well as for various types of rotator cuff tears: superior (supraspinatus), superior-anterior (supraspinatus and subscapularis), and superior-posterior (supraspinatus, infraspinatus and teres minor). Each rotator cuff tear condition was repeated after shifting the humerus and the glenohumeral joint center of rotation to represent the effect of a reverse prosthesis. Changes in compressive, shear, and total JRF were analyzed. The model compared favorably to in vivo JRF measurements, and existing clinical and biomechanical knowledge. Implanting a reverse prosthesis with a functional rotator cuff or with an isolated supraspinatus tear led to more than 2 times higher compressive JRF than with massive rotator cuff tears (superior-anterior or superior-posterior), while the shear force remained comparable. The total JRF increased more than 1.5 times. While a lower shear to compressive ratio may reduce the risk of glenosphere loosening, higher JRF might increase the risk for other failure modes such as fracture or polyethylene wear of the reverse prosthesis.